Analysis Of The Main Exchange Of Female Athletes - Atamukhamedova Mas’uda Rahimjonovna (Zien Journals, 2023)
In the article, taking into account some anthropometric indicators, the energy consumption of the body of student athletes was determined, depending on how many times a week they engage in physical training. The relationship between the energy spent by them in the main exchange and physical training was observed. In addition, according to the speed and weight of female students, the energy consumption when running 100 meters was calculated. Relevant conclusions were presented based on the obtained results.
Keywords: basic metabolism; chemical work; muscle contraction